Answer:
![\left[\begin{array}{ccc}7\\4\\2\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D7%5C%5C4%5C%5C2%5Cend%7Barray%7D%5Cright%5D)
The answer is a single-column matrix (7,4,2)
Step-by-step explanation:
In such multiplication of matrices, you have to proceed by multiplying each ROW of the first matrix by the COLUMN of the second matrix. So,
![\left[\begin{array}{ccc}3&6&1\end{array}\right] * \left[\begin{array}{ccc}2\\0\\1\end{array}\right] = (3 * 2) + (6 * 0) + (1 * 1) = 6 + 0 + 1 = 7](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D3%266%261%5Cend%7Barray%7D%5Cright%5D%20%2A%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D2%5C%5C0%5C%5C1%5Cend%7Barray%7D%5Cright%5D%20%3D%20%283%20%2A%202%29%20%2B%20%286%20%2A%200%29%20%2B%20%281%20%2A%201%29%20%3D%206%20%2B%200%20%2B%201%20%3D%207)
then...
![\left[\begin{array}{ccc}2&4&0\end{array}\right] * \left[\begin{array}{ccc}2\\0\\1\end{array}\right] = (2 * 2) + (4 * 0) + (0 * 1) = 4 + 0 + 0 = 4](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D2%264%260%5Cend%7Barray%7D%5Cright%5D%20%2A%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D2%5C%5C0%5C%5C1%5Cend%7Barray%7D%5Cright%5D%20%3D%20%282%20%2A%202%29%20%2B%20%284%20%2A%200%29%20%2B%20%280%20%2A%201%29%20%3D%204%20%2B%200%20%2B%200%20%3D%204)
and
![\left[\begin{array}{ccc}0&6&2\end{array}\right] * \left[\begin{array}{ccc}2\\0\\1\end{array}\right] = (0 * 2) + (6 * 0) + (2 * 1) = 0 + 0 + 2= 2](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D0%266%262%5Cend%7Barray%7D%5Cright%5D%20%2A%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D2%5C%5C0%5C%5C1%5Cend%7Barray%7D%5Cright%5D%20%3D%20%280%20%2A%202%29%20%2B%20%286%20%2A%200%29%20%2B%20%282%20%2A%201%29%20%3D%200%20%2B%200%20%2B%202%3D%202)
I hope it helps.
Answer:
Step-by-step explanation:
Let x represent the number of questions that Tim got right in the math test.
The number of questions that Tim got wrong in the math test is 10.
If the total number of questions on the math test is q, it means that
x + 10 = q
If he received 4 points for every correct answer and there was no penalty for wrong answers, it means that he received 0 point for a wrong answer. If
his score was 76 points, it means that
4x + 0 × 10 = 76
4x = 76
Therefore, the required equations are
x + 10 = q
4x = 76
Answer:
f(-1) = 4
Step-by-step explanation:
See below for the synthetic division tableau. The remainder is 4, hence ...
f(-1) = 4
___
IMO, in this function it is far easier just to substitute -1 for x. Since the only terms are of even degree, the value of f(-1) is the sum of the coefficients:
f(-1) = -1 +1 +4
f(-1) = 4
The answer is in the picture I’ll send u a link phs.dcsdk12.org the answer is in there good luck!
Answer:
C
Step-by-step explanation:
In five minutes it decreased by 10 gallons (5x2=10), In 10 minutes it decreased by 20 gallons.